2023
DOI: 10.1590/1807-1929/agriambi.v27n9p653-662
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation methods of Azospirillum brasilense in lettuce and arugula in the hydroponic system

Abstract: Lettuce and arugula are the most cultivated leafy vegetables in hydroponic systems in the world, and the little information about Azospirillum brasilense effects in research in this system makes it necessary to verify the best method of inoculation of these bacteria. Therefore, this study aimed to verify the beneficial effects of inoculation methods of A. brasilense on plant growth and nutrition of lettuce and arugula grown in the hydroponic system. The study was conducted in a greenhouse with 30% shading. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Therefore, our results described that growth and nutrient accumulation in hydroponic lettuce were improved with inoculation of A. brasilense strains AbV5 and AbV6 at doses between 39 and 50 mL (Figures 1, 3 and 4). The current results were supported by a previous study that verified the use of A. brasilense strains AbV5 and AbV6 increased growth and nutrient acquisition in hydroponic lettuce and arugula [13]. Plants adapt several mechanisms, such as biological nitrogen fixation, phosphate and zinc solubilization, greater root exploration, and induction of resistance to pathogens, when inoculated with A. brasilense.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, our results described that growth and nutrient accumulation in hydroponic lettuce were improved with inoculation of A. brasilense strains AbV5 and AbV6 at doses between 39 and 50 mL (Figures 1, 3 and 4). The current results were supported by a previous study that verified the use of A. brasilense strains AbV5 and AbV6 increased growth and nutrient acquisition in hydroponic lettuce and arugula [13]. Plants adapt several mechanisms, such as biological nitrogen fixation, phosphate and zinc solubilization, greater root exploration, and induction of resistance to pathogens, when inoculated with A. brasilense.…”
Section: Discussionsupporting
confidence: 89%
“…The current results showed that the shoot fresh and dry matter of hydroponic lettuce improved with increasing doses of A. brasilense when compared with non-inoculated plants (Figure 1A,C). It may be possible due to higher photosynthetic efficiency, assimilation of carbon, and nutrient acquisition by roots with the inoculation of A. brasilense [13]. It has been reported that inoculation with A. brasilense via nutrient solution at a dose of 10 mL 100 L −1 has increased the number of leaves, fresh and dry mass of shoots, and shoot growth of lettuce and arugula grown in a hydroponic system [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations